Endoplasmic reticulum stress in innate immune cells - a significant contribution to non-alcoholic fatty liver disease - Zhou, Liangliang; Shen, Haiyuan; Li, Xiaofeng; Wang, Hua (Frontiers in Immunology, 2022)
Liver disease and its complications affect millions of people worldwide. NAFLD (non-alcoholic fatty liver disease) is the liver disease associated with metabolic dysfunction and consists of four stages: steatosis with or without mild inflammation (NAFLD), non-alcoholic steatohepatitis (NASH), fibrosis, and cirrhosis. With increased necroinflammation and progression of liver fibrosis, NAFLD may progress to cirrhosis or even hepatocellular carcinoma. Although the underlying mechanisms have not been clearly elucidated in detail, what is clear is that complex immune responses are involved in the pathogenesis of NASH, activation of the innate immune system is critically involved in triggering and amplifying hepatic inflammation and fibrosis in NAFLD/NASH. Additionally, disruption of endoplasmic reticulum (ER) homeostasis in cells, also known as ER stress, triggers the unfolded protein response (UPR) which has been shown to be involved to inflammation and apoptosis. To further develop the prevention and treatment of NAFLD/NASH, it is imperative to clarify the relationship between NAFLD/NASH and innate immune cells and ER stress. As such, this review focuses on innate immune cells and their ER stress in the occurrence of NAFLD and the progression of cirrhosis.